Pemanfaatan Ruang Terbuka Hijau Publik sebagai Destinasi Wisata Tengah Kota - Tariza Noviranti Muhaling; Muhammad Roisul Basyar (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
Green Open Space (RTH) is an elongated area / path and / or group, whose use is more open, where plants grow, both naturally and intentionally planted. Currently, urban areas are intensively utilizing their green open space areas to become a tourist destination in the middle of the city. The purpose of this study is to find out how the use of green open space in this case harmony park as a tourist destination in the middle of the city. The method used in this study the author uses descriptive qualitative research methods, with data collection techniques used are documentation, previous research literature studies, interviews, and observations. As well as primary and secondary data that the author obtained from observation, documentation, and interviews. And the results obtained from this study are the use of green open space (RTH) in addition to being used to maintain balance, harmony, and beauty of the environment can also be used as a tourist attraction in the middle of the city. In this study, the use of green open space located in one of the Surabaya City Villages, namely Keputih Village. The green open space owned in Keputih Village is in the form of a park, this park was once a Landfill (TPA) which in 2013 this landfill underwent development into a park, this development was intended as a revitalization for land improvement. The use of open space in this harmony park can be said to be good, by linking aspects of tourist attraction based on the theory of Suwantoro (2004), as well as the theory of aspects of forming good quality public space described by Carr (1992).